Analysis of periodontal parameters, subgingival bacteria and levels of LL-37 in periodontitis subjects with rheumatoid arthritis / Cheah Chia Wei - Cheah, Chia Wei (2021)
Associations between rheumatoid arthritis (RA), a chronic inflammatory autoimmune disease of the joints, and periodontitis (PD), a chronic inflammatory disease affecting tooth supporting tissues have been reported. Antimicrobial peptide cathelicidin LL-37 besides being antibacterial, is also involved in inflammatory process. It has been suggested as a possible mechanistic link for these diseases. This study aimed to investigate the subgingival microbial profile of RA subjects and its correlation with levels of salivary and serum LL-37. A total of 104 subjects were allocated into RA (n=49) or non-RA (NRA) (n=55) groups. Three subgroups, PD, gingivitis (G) and periodontal health (H) were further established. Demographic, periodontal parameters and rheumatology data were collected. Subgingival plaque, saliva and serum was sampled. Extracted plaque DNA was amplified and sequenced on MiSeq platform targeting the 16s rRNA V3-V4 region. Sequenced data was processed and analysed in CLC Genomic Workbench (Qiagen) to study characteristics of bacterial communities. Correlations between bacteria were explored using network analysis and differentially abundant bacteria were investigated. Serum and salivary LL-37 levels were measured using enzyme-linked immunosorbent assay (ELISA). The associations between bacteria genera with disease parameters and LL-37 were explored. Bacterial communities were highly diverse in all groups while the samples clustered together according to PD conditions. Phyla Firmicutes, Fusobacteria, Bacteroidetes, Actinobacteria, Proteobacteria, Patescibacteria and Epsilonbacteraeota were 99% of the total abundance. In the PD groups, there were higher abundance in phyla Spirochaetes and Synergistetes and reduction in phyla Actinobacteria and Proteobateria. Highly dense inter-generic iv networks were noted between the genera in the RA-PD group compared to NRA-PD, RA?H or NRA-H. More periodontal disease-associated bacteria genera were observed in RA?PD group. For levels of salivary and serum LL-37, RA-PD showed statistically higher salivary level compared to all groups. All RA groups and NRA-PD showed statistically higher serum LL-37 levels compared to NRA-G and NRA-H, but not across the four groups. Salivary LL-37 positively correlated with ESR and negatively correlated with CAL in RA-H. Serum LL-37 negatively correlated with number of teeth in NRA-PD; RA disease duration in RA-H; positively correlated with ESR in RA-G and CRP in RA-H. Periodontal disease-associated genus positively correlated with periodontal parameters in NRA-H groups. However, in the rest of the groups, both health- and disease-associated genera correlated positively with disease parameters. For correlations with salivary and serum LL-37 similar presentations were exhibited. In conclusion, subgingival microbial profile was influenced by PD condition. The aberrant immune system in RA-PD presented as dense network of subgingival microbiota. Severe periodontitis denoted by fewer number of teeth in NRA-PD showed positive association with serum LL-37. Positive correlations for serum LL-37 with inflammation were based on associations with ESR and CRP in RA groups. A dysbiotic oral microbial community was associated with the inflammatory conditions present in RA and PD. These inflamed conditions increased the levels of circulating inflammatory cytokines such as LL-37 that may further dysregulate the host immune balance. The mechanism of subgingival microbial dysbiosis on LL-37 and the development of RA needs to be further studied. Keywords: subgingival microbiota, rheumatoid arthritis, periodontitis, LL-37